2020
DOI: 10.7307/ptt.v32i5.3443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Driving Style and Vehicle Maintenance on Vehicle Roadworthiness

Abstract: Vehicles that are non-roadworthy pose a hazard for all road users and can be one of the main causes of traffic accidents. Previous studies have analysed the impact of the driving style on environmental sustainability and road safety. Starting from this, there was a need to further investigate the relationship between the driving style and vehicle roadworthiness as well. Vehicles that do not comply with the prescribed requirements should be excluded from traffic at a periodic technical inspection. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…At the same time, periodic technical inspections of vehicles fulfil their purpose indirectly through the psychological effect that they have on vehicle operators. Awareness of the obligation to undergo a periodic technical inspection of a vehicle causes that certain defect on vehicles are being preventively fixed by the vehicle owners even before the performance of such inspection, thereby contributing in this manner to their safety as well as others [40]. Without this, they probably would not have any incentive to behave like this.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…At the same time, periodic technical inspections of vehicles fulfil their purpose indirectly through the psychological effect that they have on vehicle operators. Awareness of the obligation to undergo a periodic technical inspection of a vehicle causes that certain defect on vehicles are being preventively fixed by the vehicle owners even before the performance of such inspection, thereby contributing in this manner to their safety as well as others [40]. Without this, they probably would not have any incentive to behave like this.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Conversely, smooth and consistent driving practices can contribute to prolonged intervals between SIs and maintenance requirements. The results of the study in [59] indicated that drivers can influence the condition of their vehicles by adjusting their driving style, even with identical mileage and maintenance practices.…”
Section: Analysis Of the Impact Of Weather Conditions And Other Facto...mentioning
confidence: 99%